A new species of Mabuya (Squamata, Scincidae) from the Venezuelan Andes - Miralles, Aurélien; Rivas, Gilson; Schargel, Walter E. (Zootaxa, 2005)
Mabuya meridensis sp. nov. is described from the Cordillera de Mérida, Venezuelan Andes. This species differs from all other Mabuya species by the combined presence of seven dark and four whitish longitudinal stripes, paired frontoparietals, and forelimbs touching hindlimbs when adpressed against body. Mabuya meridensis is the second species of Mabuya to be described from the Andes. The only other species described from the Andes is M. cochabambae, native to the Inner-Andean dry valley of central Bolivia. With addition of the new species, five species of Mabuya are now known to occur in Venezuela (M. carvalhoi, M. croizati, M. falconensis, M. meridensis, and M. nigropunctata).